Research Profile of Discovery Learning in Physics Learning During the COVID-19 Pandemic - Prahani, Binar Kurnia; Jatmiko, Budi; Amelia, Tan; Neswary, Shalsa Billa Ardhana; Arzak, Kirana Aureola; Qotrunnada, Nova Allysa (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This research aims to analyze the application of discovery learning to physics learning during the COVID-19 pandemic. This research method is a study of literature and journals, as many as ten journals that can be accounted for related to the application of discovery learning research models to physics learning during the COVID-19 pandemic in Indonesia. The study was analyzed using qualitative descriptive analysis with paper review technique. It was concluded that: 1) The application of the discovery learning model to physics learning during the COVID-19 pandemic can improve student understanding, students’ critical thinking ability, and mastery of student concepts. 2) The use of online learning tools and discovery learning-based e-modules can improve students’ mastery of concepts in physics learning during the COVID-19 pandemic. 3) The advantages of the discovery learning model in physics learning during the COVID-19 pandemic are that it can improve cognitive abilities and form students’ disciplined and positive attitudes. 4) The flexibility of the discovery learning model in physics learning during the COVID-19 pandemic is that students have difficulty understanding the material, and teachers find it difficult to present the material, so the application of the discovery learning model in physics learning during the COVID-19 pandemic in Indonesia is not all effective.